2021
DOI: 10.1177/03000605211055378
|View full text |Cite
|
Sign up to set email alerts
|

Use of GP73 in the diagnosis of non-alcoholic steatohepatitis and the staging of hepatic fibrosis

Abstract: Objective To evaluate the utility of Golgi protein 73 (GP73) in the diagnosis of non-alcoholic steatohepatitis (NASH) and hepatic fibrosis (HF) staging. Methods Ninety-one patients with non-alcoholic fatty liver disease (NAFLD) were allocated to NAFL (n = 46) and NASH (n = 45) groups according to their NAFLD activity score (NAS), and there were 30 healthy controls. Serum GP73 was measured by ELISA, GP73 protein expression was evaluated using immunohistochemistry, and FibroScan was used to determine liver hardn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
(66 reference statements)
0
2
0
1
Order By: Relevance
“…Recientemente, en pacientes con cirrosis compensada, se ha observado una relación entre niveles elevados de GP73 y peores resultados clínicos, como la descompensación, el desarrollo de hepatocarcinoma, y mortalidad relacionada con patología hepática [ 93 , 94 ]. Su uso también ha sido validado en pacientes con MASLD [ 95 ], ALD y hepatitis vírica [ 64 , 88 , 96 ], lo que demuestra su utilidad para el diagnóstico de fibrosis y cirrosis avanzada, presentando un valor diagnóstico mayor que los índices FIB-4 y APRI [ 97 ].…”
Section: Biomarcadores Indirectosunclassified
“…Recientemente, en pacientes con cirrosis compensada, se ha observado una relación entre niveles elevados de GP73 y peores resultados clínicos, como la descompensación, el desarrollo de hepatocarcinoma, y mortalidad relacionada con patología hepática [ 93 , 94 ]. Su uso también ha sido validado en pacientes con MASLD [ 95 ], ALD y hepatitis vírica [ 64 , 88 , 96 ], lo que demuestra su utilidad para el diagnóstico de fibrosis y cirrosis avanzada, presentando un valor diagnóstico mayor que los índices FIB-4 y APRI [ 97 ].…”
Section: Biomarcadores Indirectosunclassified
“…Recently, it has been demonstrated that in patients with compensated cirrhosis higher levels of GP73 are related to worse outcomes such as decompensation, hepatocarcinoma development, and liver-related deaths [ 93 , 94 ]. Its use also has been validated in MASLD [ 95 ], ALD and viral hepatitis patients [ 64 , 88 , 96 ], proving to be a useful tool in the diagnosis of advanced fibrosis and cirrhosis, even better than FIB-4 or APRI [ 97 ].…”
Section: Indirect Biomarkersmentioning
confidence: 99%
“…In addition, Golm1 expression is also known to be induced in the liver of mice fed with high-fat and highcholesterol cholate diet (7). Recent study also showed a positive correlation between hepatic GOLM1 mRNA expression and nonalcoholic steatohepatitis (NASH) (9). GOLM1 enhances metastasis by acting as a cargo adaptor protein for epidermal growth factor receptor recycling and signaling (10).…”
mentioning
confidence: 99%